2020
DOI: 10.1080/07060661.2020.1777465
|View full text |Cite
|
Sign up to set email alerts
|

Systemic colonization of potato plants resulting from potato haulm inoculation with Dickeya solani or Pectobacterium parmentieri

Abstract: In two glasshouse experiments, colonization of potato (Solanum tuberosum L.) plants by the bacterial pathogens Dickeya solani and Pectobacterium parmentieri was studied after leaf infection. Leaves, whether or not artificially wounded, were spray-inoculated with various densities of green-fluorescent protein tagged strains of the pathogens, avoiding contamination of soil during inoculation. Microscopy analysis indicated that both pathogens were able to penetrate and colonize hydathodes, stomata and wounds of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Together with other SRP species causing diseases of crops, P. parmentieri (formerly known as Erwinia carotovora subsp. wasabiae and later P. wasabiae ) has recently been recognized as an increasing threat for potato cultivation [ 6 , 7 , 8 ]. This species was first described as a pathogen in 2010, causing severe potato blackleg outbreaks in field-grown crops in New Zealand [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with other SRP species causing diseases of crops, P. parmentieri (formerly known as Erwinia carotovora subsp. wasabiae and later P. wasabiae ) has recently been recognized as an increasing threat for potato cultivation [ 6 , 7 , 8 ]. This species was first described as a pathogen in 2010, causing severe potato blackleg outbreaks in field-grown crops in New Zealand [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the development of new genome-based taxonomic classification techniques, it has become evident that many bacteria previously characterized as Pectobacterium carotovorum that were isolated from crops in Europe and elsewhere should be currently re-classified as P. parmentieri [ 11 ]. In the last ten years, the dominant role of P. parmentieri in the epidemiology of potato blackleg and soft rot diseases in Europe and worldwide has been widely recognized [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results suggested that D. solani colonizes potato and S. dulcamara plants in a very similar manner, as it was evidenced after infection that the bacteria used vascular tissue to systemically spread inside both plant species and cause visually similar symptoms in culture-tube grown plants [ 107 ]. Recently, Kastelein et al [ 104 ] assessed the spread of GFP-tagged D. solani and Pectobacterium parmentieri strains inside potato plants after spray-inoculation of wounded and intact potato leaves. The GFP-tagged bacteria belonging to both species were detected in distantly located plant parts, indicating that upon favorable conditions, the SRP bacteria can probably pose a risk for the next generation of crop cultivation [ 104 ].…”
Section: Colonization Of Plants By Fluorescent Protein-tagged mentioning
confidence: 99%
“…Recently, Kastelein et al [ 104 ] assessed the spread of GFP-tagged D. solani and Pectobacterium parmentieri strains inside potato plants after spray-inoculation of wounded and intact potato leaves. The GFP-tagged bacteria belonging to both species were detected in distantly located plant parts, indicating that upon favorable conditions, the SRP bacteria can probably pose a risk for the next generation of crop cultivation [ 104 ]. In the aforementioned studies, GFP tagging was done to support the observations on the spread of bacterial pathogens in host plants.…”
Section: Colonization Of Plants By Fluorescent Protein-tagged mentioning
confidence: 99%
“…In some studies, disease outbreaks were related to the usage of contaminated irrigation water [ 17 ]. Kastelein et al [ 18 ] reported that spray inoculation of potato leaves with 10 2 CFU/mL D . solani resulted in diseased plants in greenhouse experiments.…”
Section: Introductionmentioning
confidence: 99%